2000
DOI: 10.1097/00000658-200012000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brain Death and Hemodynamic Status on Function and Immunologic Activation of the Potential Donor Liver in the Rat

Abstract: ObjectiveTo assess the effect on the function and immunologic status of potential donor livers of the duration of brain death combined with the presence and absence of hemodynamic instability in the donor. Summary Background DataBrain death, regarded as a given condition in organ transplantation, could have significant effects on the donor organ quality. MethodsBrain death was induced in Wistar rats. Short or long periods of brain death in the presence or absence of hemodynamic instability were applied. Sham-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 25 publications
(21 reference statements)
6
86
0
3
Order By: Relevance
“…A hypotensive period after the catecholamine-induced peak has been described in most studies using a sudden onset model , Bittner et al 1995, Chen et al 1996, Herijgers et al 1996, van der Hoeven et al 2000. In our experiments, the peak in blood pressure occurred, followed by a plateau at levels above 100 mmHg ( Figure 1B).…”
Section: Discussionsupporting
confidence: 75%
“…A hypotensive period after the catecholamine-induced peak has been described in most studies using a sudden onset model , Bittner et al 1995, Chen et al 1996, Herijgers et al 1996, van der Hoeven et al 2000. In our experiments, the peak in blood pressure occurred, followed by a plateau at levels above 100 mmHg ( Figure 1B).…”
Section: Discussionsupporting
confidence: 75%
“…CINC-3, a chemokine synonymous to rat macrophage inflammatory protein-2 (MIP-2), is strongly chemotactic for neutrophils and known to elicit a neutrophilic inflammatory response (30). These data explain the previous observation of increased neutrophilic infiltration in liver and kidneys within 6 h after brain death in the rat (17,26).…”
Section: Discussionmentioning
confidence: 55%
“…The donor BAL IL-8 concentration correlated with recipient graft function (7). Similar immune activation has been demonstrated in other organs with controlled animal experiments (17,26). However, cytokine responses in the lung have not been investigated in brain death models or in NPE.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In 1995, Terasaki et al 3 showed that graft survival for living unrelated donation is superior compared to deceased donation. This thought to be due to numerous pathophysiologic changes that occur in brain death that potentially contribute to DGF in the transplanted kidney 4 .…”
Section: Commentarymentioning
confidence: 99%